2020
DOI: 10.1371/journal.pone.0237665
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of low-dose colchicine on inflammatory biomarkers, lipids, blood count and renal function in chronic coronary artery disease and elevated high-sensitivity C-reactive protein

Abstract: Inflammation plays a pivotal role in atherothrombosis. Colchicine is an anti-inflammatory drug that may attenuate this process. Cardiovascular protective effects of anti-inflammatory drugs, however, seem to be limited to patients with a biochemical response. We therefore investigated whether short-term exposure to colchicine reduced inflammatory markers and whether additional laboratory changes occur in patients with chronic coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 40 publications
3
39
0
Order By: Relevance
“…Cardiovascular benefits of canakinumab were largest among those who achieved lowest levels of hs-CRP and IL-6 [47,48]. We previously showed a reduction in hs-CRP and IL-6 following 30 days of colchicine treatment in patients with chronic coronary disease and hs-CRP above 2 mg/L [49]. In the current study, with no hs-CRP criteria on inclusion, we also observed a reduction in hs-CRP.…”
Section: Nlrp3 In Coronary Disease and The Effects Of Colchicine On Inflammatory Markerssupporting
confidence: 72%
“…Cardiovascular benefits of canakinumab were largest among those who achieved lowest levels of hs-CRP and IL-6 [47,48]. We previously showed a reduction in hs-CRP and IL-6 following 30 days of colchicine treatment in patients with chronic coronary disease and hs-CRP above 2 mg/L [49]. In the current study, with no hs-CRP criteria on inclusion, we also observed a reduction in hs-CRP.…”
Section: Nlrp3 In Coronary Disease and The Effects Of Colchicine On Inflammatory Markerssupporting
confidence: 72%
“…For example, the LoDoCo2 trial 9 showed the efficacy of low-dose colchicine (also tested in the COLCOT trial 7 ) for the secondary prevention of cardiovascular events in patients with stable coronary artery disease. This effect was associated with a reduction in the circulating levels of hsCRP and of proteins involved in the activation of the NLRP3 inflammasome 10 , 11 . However, treatment with colchicine did not reduce the risk of cardiovascular death, and the incidences of death from any cause and non-cardiovascular death were higher in the colchicine-treated group than in the placebo group.…”
Section: Introductionmentioning
confidence: 99%
“…Colchicine is well known as an anti-inflammatory drug used in the treatment of acute gouty arthritis, familial Mediterranean fever and Behçet’s disease 1 . Additionally, it has been used for the treatment of pericarditis 2 , atrial fibrillation post-coronary bypass, stroke and for secondary prevention of cardiac events 3 7 . More recently it has been investigated in the setting of coronary artery disease (CAD) 8 11 .…”
Section: Introductionmentioning
confidence: 99%